Radio Freedom worker G.Mqwebu in the RF-studio in Zambia with the equipment donated by 'Broadcasting for Radio Freedom' - Goijaerts, Inge,
Radio Freedom worker G.Mqwebu in the RF-studio in Zambia with the equipment donated by 'Broadcasting for Radio Freedom'.